Peran Organizational Citizenship Behavior (OCB) Dalam Menurunkan Stress Kerja - Andi Hendrawan; Hari Sucahyowati; Indriyani Indriyani; Kristian Cahyandi (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2020)
The main threat to modern organizations today is work stress, which has the potential to have a negative impact on employees and the organization. The impact of work stress, among others: work stress tends to make employee performance will decrease. Second, employee performance will not be optimal if experiencing heavy pressure at work. Third, work stress tends to make employees lazy to work so often absent. Fourth, employees often leave work without permission due to uncomfortable working conditions. Fifth, employees have a desire to leave the job because the workload is quite heavy. The purpose of this study is to prove that organizational citizenship behavior (OCB) affects work stress. The role of Organizational citizenship behavior (OCB) in reducing work stress in PT MK employees is significant, this is indicated by the influence of OCB on work stress, with a regression test with y = -0,756x + 60,038 with y = job stress and x = OCB, P value = 0.00 also means that the correlation between OCB and work stress is very significant. Contribution of OCB's influence on work stress by 77.9%. OCB's dominant behavior on employees will reduce work stress so that organizational goals will be achieved, namely optimal performance.